Goblet Cell Adenocarcinoma of Appendix with Ovarian Metastasis: A Case Report - P Archana; Priyathersini Nagarajan; R Priya Dharshini; S Jagadesh Chandra Bose (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Goblet Cell Adenocarcinoma (GCA) is a rare neoplasm of the appendix composed of goblet like mucinous cells, classified as adenocarcinoma. High-grade GCA of appendix with large aggregates of mucin containing goblet shaped cells, secondarily involving the ovary with signet ring cells is very rare. Such cases pose a significant diagnostic challenge, as the pelvic mass may clinically mimic as a primary ovarian malignancy, thereby delaying identification of the true appendiceal origin. This is a case of 50-year-old postmenopausal female who presented with complaints of significant weight loss (5 kg) since one month and recurrent vomiting since one month. Clinical examination revealed a large pelvic mass. Ultrasonography of abdomen and pelvis revealed malignant neoplasm in pelvis with involvement of uterine stump and vagina. Biopsy of the pelvic mass showed malignancy, however, the primary site remained inconclusive, necessitating further workup to exclude a gastrointestinal/gynaecological primary. The patient underwent surgical exploration. Histopathological examination of appendix demonstrated tumour cells arranged in anastomosing trabeculae, irregular nests, glands and cords with singled out goblet-shaped mucin-secreting cells and areas of high-grade transformation showing signet ring cell morphology. Histopathological examination of ovarian mass showed mucin filled signet ring cells. Individual tumour cells showed abundant intracytoplasmic (cellular) mucin with basally displaced, mildly to moderately pleomorphic nuclei. Immunohistochemistry showed positivity for CK20, CDX2, SATB2, CK19, synaptophysin; CK7 and PAX8 were negative, confirming primary appendiceal origin. This immunophenotype excludes primary ovarian mucinous carcinoma and confirms ovarian metastasis consistent with Krukenberg tumour. This case highlights the diagnostic pitfall of misinterpreting appendiceal GCA as a primary ovarian malignancy when the patient presents with a pelvic mass. High-grade transformation with signet ring cell features carries a poor prognosis requiring immediate management. This case is unique because of a grossly normal-appearing appendix despite underlying malignancy, presenting as a primary ovarian mass. The diagnostic difficulty due to high-grade transformation with signet ring cell morphology highlights the need for broad spectrum immunohistochemistry panel before labelling a pelvic mass as primary ovarian in origin.